Social associations, relatedness and population genetic structure of killer whales (Orcinus orca) in Iceland - Tavares, Sara de Brito (University of St Andrews, 2017)
In killer whales, fish- versus mammal-eating ecological differences are regarded as key ecological drivers of sociality, but the potential influence of specific target prey characteristics remains unclear. This thesis aimed to study the social patterns and dynamics of Icelandic killer whales feeding upon herring, a schooling prey that undergoes frequent changes in distribution and school size. I used a multi-disciplinary approach combining photo-identification and genetic data to understand the sociality, role of kinship and genetic differentiation within the population. Individuals sighted in summer-spawning and overwintering herring grounds during at least five separate days (N = 198) were considered associated if photographed within 20 seconds of each other. Photo-identified individuals were genotyped (N = 61) for 22 microsatellites and mitochondrial DNA control region (611 bp). The population had weak but non-random associations, fission-fusion dynamics at the individual level and seasonal patterns of preferred associations. The society was significantly structured but not hierarchically. Social clusters were highly diverse and, whilst kinship was correlated with association, it was not a prerequisite for social membership. Indeed, some cluster members had different mitochondrial haplotypes, representing separate maternal lineages. Individuals with different observed movement patterns were genetically distinct, but associated with each other. No sex-biased dispersal or inbreeding was detected. This study revealed that the Icelandic population has a multilevel society without clear hierarchical tiers or nested coherent social units, different from the well-studied salmon- (‘residents’) and seal-eating populations in the Northeast Pacific. In the Icelandic population kinship drives social structure less strongly than in residents. These findings suggest effective foraging on schooling herring in seasonal grounds promotes the formation of flexible social groupings which can include non-kin. Killer whale ...